Piezocone-based prediction of secondary compression settlements of coastal defence structures on natural silt mixtures. (1st April 2016) - Tonni, Laura; García Martínez, María Fernanda; Simonini, Paolo; Gottardi, Guido
Abstract: This paper discusses the evaluation of long-term settlements of a predominantly silty seabed under a rubble mound breakwater using a simplified one-dimensional approach in conjunction with an empirical method for the estimate of one-dimensional creep characteristics of soils from cone penetration test data. In particular, the procedure is applied to the assessment of long-term settlements of two existing breakwaters built along the Venetian coastline as part of the coastal defence works included in the ambitious Mo.S.E. project for the temporary closure of the lagoon inlets. The effectiveness of two different CPTU-based empirical correlations for the estimate of the secondary compression index C αε in sand and silt mixtures, recently calibrated on field data from a Test Site located in the Venetian Lagoon area, has been examined by comparing the computed settlements with actual vertical displacements obtained from Persistent Scatterer Interferometry (PSI). The paper aims at providing some practical guidance on the assessment of long-term settlements in soft soil deposits of different coastal areas, by illustrating a general and simple approach for the evaluation of secondary compression characteristics of a large variety of sediments, based on the use of a site investigation technique routinely employed in nearshore and offshore projects. Highlights: Long-term settlements of a silty seabed under a breakwater are evaluated. The 1-D creep characteristics of soils are estimated from piezocone (CPTU) tests. The effectiveness of two different empirical CPTU-based correlations is examined. Predicted settlements of breakwaters are compared with monitored displacements. Practical guidance for evaluating long-term settlements in soft soils is proposed.